The consistency control of mold level in casting process. (May 2017) - Shen, Ping; Li, Han-Xiong
Abstract: A new multiple periodic disturbance rejection control for casting process is proposed in this paper. Firstly, a high-precision multiple periodic disturbance detection method is designed. The accurate frequencies of the disturbance can be obtained. By using the disturbance observer and a group of filters with additional delay items, multiple periodic disturbance can be suppressed under time-delay environment. Then systematic control design is achieved based on the robust stability analysis. Finally, the efficiency of the proposed method is shown by comparisons between different methods and time-varying disturbance rejection in the consistency control of mold level. Highlights: A multiple frequency disturbance rejection control for casting process is proposed. The robustness of the proposed control method is analyzed. The controller is designed based on robustness analysis. The comparison studies of the proposed method show the efficiency.